Preparation method and application of MoS2 / Fe2O3@Fe-MOF modified carbon electrode
By using MoS2/Fe2O3@Fe-MOF to modify the carbon electrode in the bioelectric Fenton system, the problems of low cathode catalytic performance and complex electrode material preparation are solved, and efficient pollutant degradation and cost reduction are achieved.
Patent Information
- Application Number
- CN202510008048.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The cathode in the existing bioelectric Fenton system has low catalytic performance in the generation and activation of H2O2, poor performance in degrading pollutants, and complex preparation of electrode materials and high cost.
Through the regulation of hydrothermal reaction solvent, the dissolved Fe is converted into Fe2O3 in the preparation of MOF, the electron density of Fe2+/Fe3+ is regulated, its catalytic performance of electrofenton is increased, and the conductive properties are improved through the recombination of MoS2, and the redox cycle of Fe2+/Fe3+ is promoted.
The catalytic performance of the cathode on H2O2 is improved, the pollutant degradation ability is enhanced, the preparation process of electrode materials is simplified, and the cost is reduced.
Smart Images

Figure CN119409314B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a MoS 2 / Fe 2 O 3 @Preparation method and application of Fe-MOF modified carbon electrode. Background Art
[0002] With the development of society and the expansion of industrial scale, the types and discharge of wastewater are increasing, and a large number of highly toxic and difficult to degrade pollutants are emerging. Antibiotics, as the most widely used drugs, are widely used to prevent and treat diseases worldwide. Since antibiotics cannot be completely degraded in the digestive tract of humans and animals, they will enter the environment with excrement. The introduction of these exogenous compounds will not only cause continuous pollution to aquatic and terrestrial ecosystems, but also cause bacteria in nature to have drug resistance. The increase and spread of drug resistance of environmental pathogens will inevitably pose a threat to human public health. In order to ensure the ecological safety of the water environment, it is urgent to develop efficient wastewater treatment technology.
[0003] The bio-electro-Fenton (BEF) system is an emerging water treatment technology that combines Fenton technology, electrochemical technology and biotechnology. It has the advantages of mild operating conditions, low sludge production, high pollutant removal efficiency and low energy consumption, and has good application prospects in the field of wastewater treatment. In the bio-electro-Fenton system, the cathode often plays a crucial role, which is related to the online generation of H by the two-electron reduction of oxygen. 2 O 2 ; It is also related to H 2 O 2 The decomposition of H produces reactive oxygen species (ROS) to degrade organic pollutants. The cathode in the traditional bio-Fenton system mainly consists of iron and its oxide-loaded graphite, carbon felt, carbon fiber, carbon nanotubes, etc. The above materials have the advantages of good conductivity, corrosion resistance, and low price. However, the H 2 O 2 Low yield; H 2 O 2 The activation efficiency is limited and the degradation performance is not ideal. At present, metal organic framework (Fe-MOF) materials have high specific surface area and adjustable pore structure, which can accelerate electron migration and Fe 2+ Regeneration, efficient generation and activation of H 2 O 2 , becoming a very promising catalytic material in electro-Fenton catalysis, but polar solvents and high temperatures in the preparation of MOF will lead to the dissolution of the central metal Fe and reduce the catalytic activity.
[0004] Therefore, constructing a low-cost cathode with dual catalytic properties of electrocatalysis and Fenton catalysis, good conductivity and excellent stability is a core issue that needs to be solved to improve the performance of the bio-electro-Fenton system in treating pollutants and promote its practical application. Summary of the invention
[0005] Based on this, the present invention provides a MoS 2 / Fe 2 O 3 @The preparation method and application of Fe-MOF modified carbon electrode, through the regulation of hydrothermal reaction solvent, the dissolved Fe is converted into Fe in the preparation of MOF in one step 2 O 3 , regulating Fe 2+ / Fe 3+ The electron density of MoS increases its electro-Fenton catalytic performance. 2 The composite can improve Fe 2 O 3 @Fe-MOF has a conductive property that improves the electron transfer rate; and through Mo 4+ / Mo 6+ The circulation of Fe 2+ / Fe 3+ The redox cycle of the cathode enhances the catalytic performance of electro-Fenton. 2 O 2 There are many problems, such as low catalytic performance in the generation and activation of ions, unsatisfactory performance in degrading pollutants, complex preparation of electrode materials and high cost.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides a MoS 2 / Fe 2 O 3 The preparation method of @Fe-MOF modified carbon electrode comprises the following steps:
[0007] S1: Add trivalent iron salt to deionized water, stir to dissolve, add ethanol and N,N-dimethylformamide DMF to mix, then add trimesic acid, stir to dissolve, add polyvinyl pyrrolidone K30, stir at room temperature for 60 min, transfer to the reactor for hydrothermal reaction, cool naturally to room temperature after the reaction, centrifuge, wash and dry the separated solid to obtain Fe 2 O 3 @Fe-MOF powder;
[0008] S2: After natural molybdenite is ball-milled and sieved into powder, it is added into isopropyl alcohol (IPA) and ultrasonically exfoliated to obtain isopropyl alcohol (IPA)-MoS 2 Nanosheet dispersion;
[0009] S3: Fe obtained from S12 O 3 IPA-MoS obtained by adding Fe-MOF powder to S2 2 The nanosheet dispersion was ultrasonically mixed for 30-90 minutes to obtain MoS 2 / Fe 2 O 3 @Fe-MOF composite material dispersion;
[0010] S4: MoS obtained from S3 2 / Fe 2 O 3 After the Fe-MOF composite material dispersion was ultrasonically mixed with ethanol, carbon black and perfluorosulfonic acid polymer Nafion D520 were added, stirred for 30-90 min, coated on the carbon electrode surface, and dried at room temperature to obtain MoS 2 / Fe 2 O 3 @Fe-MOF modified carbon electrode.
[0011] Preferably, in S1, the trivalent iron salt is FeCl 3 6H 2 O or Fe(NO) 3 9H 2 O.
[0012] Preferably, in S1, the concentration of the deionized water solution of the ferric salt is 75-100 mol / L, the volume ratio of the deionized water, ethanol and N,N-dimethylformamide is 1:1:1, the amount ratio of the ferric salt and trimesic acid is 1.5-2:1, and the concentration of the polyvinylpyrrolidone K30 in the solution is 20 g / L.
[0013] Preferably, in S1, the temperature of the hydrothermal reaction is 150-170° C., and the time is 3-12 h.
[0014] Preferably, in S2, the particle size of the natural molybdenum ore powder is ≤20 μm, the solid-liquid ratio of the natural molybdenum ore powder to isopropyl alcohol IPA is 1:200, and the isopropyl alcohol IPA-MoS 2 The concentration of the nanosheet dispersion was 171 mg / L.
[0015] Preferably, in S2, the power of ultrasonic stripping is 350 W and the time is 24 h.
[0016] Preferably, in the S3, MoS 2 In MoS 2 / Fe 2 O 3 @The doping ratio of Fe-MOF composite materials is 0.5-2%.
[0017] Preferably, in the S4, MoS 2 / Fe 2 O 3 The volume ratio of the Fe-MOF composite material dispersion to ethanol is 1:0.07-3.5; carbon black and MoS 2 / Fe 2 O 3 The mass ratio of @Fe-MOF composite material is 0.25-0.3:1; the perfluorosulfonic acid polymer NafionD520 and MoS 2 / Fe 2 O 3 @The mass ratio of Fe-MOF composite material is 1-1.3:1.
[0018] Preferably, in S4, the carbon electrode is a carbon plate, carbon felt or carbon cloth.
[0019] Based on the same inventive concept, the present invention also provides a MoS 2 / Fe 2 O 3 @Fe-MOF modified carbon electrode application, the MoS 2 / Fe 2 O 3 @Fe-MOF modified carbon electrode is used as cathode in bio-Fenton system to degrade antibiotics in wastewater.
[0020] The above one or more technical solutions of the present invention have the following technical effects:
[0021] 1) MoS 2 / Fe 2 O 3 @Fe-MOF modified carbon electrode has adjustable ratio of iron oxide and MOF. 2 O 3 Synergistic regulation of adsorption and Fenton catalytic performance of electrode materials with Fe-MOF;
[0022] 2) Ultrasonic mixing of MoS 2 Modification on the surface of MOF can be easily achieved without the need for special instruments or complicated operation procedures. 2 Controlling the amount of promoters can prevent the agglomeration of MoS 2 The composite makes the electrode electrical performance better, accelerates electron transfer, reduces the cathode overpotential, and MoS 2 The doping of O can change the spin density distribution of C electrode in favor of O 2 Two-electron reduction of
[0023] 3) The promoter MoS used in the present invention 2Two-dimensional nanosheets are derived from the direct exfoliation of molybdenite, with low material cost, abundant sources, simple preparation process, strong controllability and low equipment requirements;
[0024] 4) The composite electrode prepared by the present invention is applied to the BEF system, has high power density, good electron transmission performance, excellent degradation performance for antibiotics, and can be recycled for many times. It has a very broad application prospect in the field of electro-Fenton. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.
[0026] Figure 1 、MoS 2 / Fe 2 O 3 @Preparation process of Fe-MOF modified carbon electrode;
[0027] Figure 2 , Fe prepared in step S1 of Examples 1 to 4 2 O 3 @XRD pattern of Fe-MOF;
[0028] Figure 3 , MoS prepared in Example 1 2 / Fe 2 O 3 @SEM image of Fe-MOF;
[0029] Figure 4 , MoS prepared in Example 1 2 / Fe 2 O 3 @TEM image of Fe-MOF;
[0030] Figure 5 , MoS prepared in Example 1 2 / Fe 2 O 3 @XRD pattern of Fe-MOF;
[0031] Figure 6 , power density curves of the materials prepared in Examples 1 to 6 and Comparative Examples 1 and 2;
[0032] Figure 7 , CV graphs of the materials prepared in Example 1 and Comparative Example 1 and Comparative Example 2;
[0033] Figure 8 , EIS spectra of the materials prepared in Example 1 and Comparative Example 1 and Comparative Example 2;
[0034] Fig. 9, Degradation curves of the materials prepared by Examples 1, 5, 6 and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0035] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0036] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as the meaning commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence. 2 / Fe 2 O 3 The preparation process of Fe-MOF modified carbon electrode is as follows Figure 1 shown.
[0037] Example 1
[0038] A MoS 2 / Fe 2 O 3 The preparation method of @Fe-MOF modified carbon electrode comprises the following steps:
[0039] S1: 1.5 mol FeCl 3 6H 2 O was added to 20 ml of deionized water, stirred and dissolved, 20 ml of ethanol and 20 ml of N, N-dimethylformamide DMF were added and mixed, and then 1 mol of trimesic acid was added and stirred and dissolved, and 1.2 g of polyvinyl pyrrolidone K30 was added. After stirring at room temperature for 60 min, the mixture was transferred to a reactor for hydrothermal reaction at 160 ° C for 3 h. After the reaction was completed, the mixture was naturally cooled to room temperature and centrifuged. The separated solid was washed and dried to obtain Fe 2 O 3 @Fe-MOF powder;
[0040] S2: After natural molybdenite was ball-milled and sieved into a powder with a particle size of ≤20 µm, 0.5 g was added to 100 ml of isopropanol (IPA) and subjected to ultrasonic exfoliation at an ultrasonic power of 400 W for 24 h to obtain isopropanol (IPA)-MoS with a concentration of 171 mg / L. 2 Nanosheet dispersion;
[0041] S3: Place 0.055 g Fe 2 O 3Add Fe-MOF powder to 3.25 ml IPA-MoS 2 The nanosheet dispersion was ultrasonically mixed for 30-90 minutes to obtain MoS 2 / Fe 2 O 3 @Fe-MOF composite material dispersion;
[0042] S4: MoS obtained from S3 2 / Fe 2 O 3 After ultrasonically mixing the Fe-MOF composite material dispersion with 3.75 ml ethanol, 0.015 g carbon black and 50 μl perfluorosulfonic acid polymer Nafion D520 were added, and stirring was continued for 30-90 minutes. The mixed solution was coated on the surface of the carbon plate and dried at room temperature to obtain MoS 2 / Fe 2 O 3 @Fe-MOF modified carbon electrode, in which MoS 2 In MoS 2 / Fe 2 O 3 @The doping ratio of Fe-MOF composite material is 1%.
[0043] Example 2
[0044] A MoS 2 / Fe 2 O 3 The preparation method of @Fe-MOF modified carbon electrode comprises the following steps:
[0045] S1: 1.6 mol FeCl 3 6H 2 O was added to 20 ml of deionized water, stirred and dissolved, 20 ml of ethanol and 20 ml of N, N-dimethylformamide DMF were added and mixed, and then 1 mol of trimesic acid was added and stirred and dissolved, and 1.2 g of polyvinyl pyrrolidone K30 was added. After stirring at room temperature for 60 min, the mixture was transferred to a reactor for hydrothermal reaction at 160 ° C for 6 h. After the reaction was completed, the mixture was naturally cooled to room temperature and centrifuged. The separated solid was washed and dried to obtain Fe 2 O 3 @Fe-MOF powder;
[0046] S2: After natural molybdenite was ball-milled and sieved into a powder with a particle size of ≤20 µm, 0.5 g was added to 100 ml of isopropanol (IPA) and subjected to ultrasonic exfoliation at an ultrasonic power of 400 W for 24 h to obtain isopropanol (IPA)-MoS with a concentration of 171 mg / L. 2 Nanosheet dispersion;
[0047] S3: Place 0.055 g Fe 2 O 3 Add Fe-MOF powder to 3.25 ml IPA-MoS 2 The nanosheet dispersion was ultrasonically mixed for 30-90 minutes to obtain MoS 2 / Fe 2 O 3 @Fe-MOF composite material dispersion;
[0048] S4: MoS obtained from S3 2 / Fe 2 O 3 After the Fe-MOF composite material dispersion was ultrasonically mixed with 3.75 ml of ethanol, 0.015 g of carbon black and 50 μl of perfluorosulfonic acid polymer Nafion D520 were added, and stirring was continued for 30-90 minutes. The mixed solution was coated on the surface of the carbon plate and dried at room temperature to obtain MoS 2 / Fe 2 O 3 @Fe-MOF modified carbon electrode, in which MoS 2 In MoS 2 / Fe 2 O 3 @The doping ratio of Fe-MOF composite material is 1%.
[0049] Example 3
[0050] A MoS 2 / Fe 2 O 3 The preparation method of @Fe-MOF modified carbon electrode comprises the following steps:
[0051] S1: 1.8 mol FeCl 3 6H 2 O was added to 20 ml of deionized water, stirred and dissolved, 20 ml of ethanol and 20 ml of N, N-dimethylformamide DMF were added and mixed, and then 1 mol of trimesic acid was added and stirred and dissolved, and 1.2 g of polyvinyl pyrrolidone K30 was added. After stirring at room temperature for 60 min, the mixture was transferred to a reactor for hydrothermal reaction at 160 ° C for 9 h. After the reaction was completed, the mixture was naturally cooled to room temperature and centrifuged. The separated solid was washed and dried to obtain Fe 2 O 3 @Fe-MOF powder;
[0052] S2: After natural molybdenite was ball-milled and sieved into powder, 0.5 g was added to 100 ml of isopropanol IPA and ultrasonically exfoliated at an ultrasonic power of 400 W for 24 h to obtain isopropanol IPA-MoS with a concentration of 171 mg / L. 2 Nanosheet dispersion;
[0053] S3: Place 0.055 g Fe 2 O 3 Add Fe-MOF powder to 3.25 ml IPA-MoS 2 The nanosheet dispersion was ultrasonically mixed for 30-90 minutes to obtain MoS 2 / Fe 2 O 3 @Fe-MOF composite material dispersion;
[0054] S4: MoS obtained from S3 2 / Fe 2 O 3 After the Fe-MOF composite material dispersion was ultrasonically mixed with 3.75 ml of ethanol, 0.015 g of carbon black and 50 μl of perfluorosulfonic acid polymer Nafion D520 were added, and stirring was continued for 30-90 minutes. The mixed solution was coated on the surface of the carbon plate and dried at room temperature to obtain MoS 2 / Fe 2 O 3 @Fe-MOF modified carbon electrode, in which MoS 2 In MoS 2 / Fe 2 O 3 @The doping ratio of Fe-MOF composite material is 1%.
[0055] Example 4
[0056] A MoS 2 / Fe 2 O 3 The preparation method of @Fe-MOF modified carbon electrode comprises the following steps:
[0057] S1: 2 mol FeCl 3 6H 2 O was added to 20 ml of deionized water, stirred and dissolved, and then 20 ml of ethanol and 20 ml of N, N-dimethylformamide DMF were added and mixed, and then 1 mol of trimesic acid was added and stirred and dissolved, and then 1.2 g of polyvinyl pyrrolidone K30 was added. After stirring at room temperature for 60 min, the mixture was transferred to a reactor for hydrothermal reaction at 160 ° C for 12 h. After the reaction was completed, the mixture was naturally cooled to room temperature and centrifuged. The separated solid was washed and dried to obtain Fe 2O 3 @Fe-MOF powder;
[0058] S2: After natural molybdenite was ball-milled and sieved into powder, 0.5 g was added to 100 ml of isopropanol IPA and ultrasonically exfoliated at an ultrasonic power of 400 W for 24 h to obtain isopropanol IPA-MoS with a concentration of 171 mg / L. 2 Nanosheet dispersion;
[0059] S3: Place 0.055 g Fe 2 O 3 Add Fe-MOF powder to 3.25 ml IPA-MoS 2 The nanosheet dispersion was ultrasonically mixed for 30-90 minutes to obtain MoS 2 / Fe 2 O 3 @Fe-MOF composite material dispersion;
[0060] S4: MoS obtained from S3 2 / Fe 2 O 3 After the Fe-MOF composite material dispersion was ultrasonically mixed with 3.75 ml of ethanol, 0.015 g of carbon black and 50 μl of perfluorosulfonic acid polymer Nafion D520 were added, and stirring was continued for 30-90 minutes. The mixed solution was coated on the surface of the carbon plate and dried at room temperature to obtain MoS 2 / Fe 2 O 3 @Fe-MOF modified carbon electrode, in which MoS 2 In MoS 2 / Fe 2 O 3 @The doping ratio of Fe-MOF composite material is 1%.
[0061] Example 5
[0062] A MoS 2 / Fe 2 O 3 The preparation method of @Fe-MOF modified carbon electrode comprises the following steps:
[0063] S1: 1.5 mol FeCl 3 6H 2O was added to 20 ml of deionized water, stirred and dissolved, 20 ml of ethanol and 20 ml of N, N-dimethylformamide DMF were added and mixed, and then 1 mol of trimesic acid was added and stirred and dissolved, and 1.2 g of polyvinyl pyrrolidone K30 was added. After stirring at room temperature for 60 min, the mixture was transferred to a reactor for hydrothermal reaction at 160 ° C for 3 h. After the reaction was completed, the mixture was naturally cooled to room temperature and centrifuged. The separated solid was washed and dried to obtain Fe 2 O 3 @Fe-MOF powder;
[0064] S2: After natural molybdenite was ball-milled and sieved into a powder with a particle size of ≤20 µm, 0.5 g was added to 100 ml of isopropanol (IPA) and subjected to ultrasonic exfoliation at an ultrasonic power of 400 W for 24 h to obtain isopropanol (IPA)-MoS with a concentration of 171 mg / L. 2 Nanosheet dispersion;
[0065] S3: Place 0.055 g Fe 2 O 3 Add Fe-MOF powder to 1.61 ml IPA-MoS 2 The nanosheet dispersion was ultrasonically mixed for 30-90 minutes to obtain MoS 2 / Fe 2 O 3 @Fe-MOF composite material dispersion;
[0066] S4: MoS obtained from S3 2 / Fe 2 O 3 After the Fe-MOF composite material dispersion was ultrasonically mixed with 5.39 ml of ethanol, 0.015 g of carbon black and 50 μl of perfluorosulfonic acid polymer Nafion D520 were added, and the mixture was continued to be stirred for 30-90 minutes. The mixture was coated on the surface of the carbon plate and dried at room temperature to obtain MoS 2 / Fe 2 O 3 @Fe-MOF modified carbon electrode, in which MoS 2 In MoS 2 / Fe 2 O 3 @The doping ratio of Fe-MOF composite material is 0.5%.
[0067] Example 6
[0068] A MoS 2 / Fe 2 O 3 The preparation method of @Fe-MOF modified carbon electrode comprises the following steps:
[0069] S1: 1.5 mol FeCl 3 6H 2 O was added to 20 ml of deionized water, stirred and dissolved, 20 ml of ethanol and 20 ml of N, N-dimethylformamide DMF were added and mixed, and then 1 mol of trimesic acid was added and stirred and dissolved, and 1.2 g of polyvinyl pyrrolidone K30 was added. After stirring at room temperature for 60 min, the mixture was transferred to a reactor for hydrothermal reaction at 160 ° C for 3 h. After the reaction was completed, the mixture was naturally cooled to room temperature and centrifuged. The separated solid was washed and dried to obtain Fe 2 O 3 @Fe-MOF powder;
[0070] S2: After natural molybdenite was ball-milled and sieved into a powder with a particle size of ≤20 µm, 0.5 g was added to 100 ml of isopropanol (IPA) and subjected to ultrasonic exfoliation at an ultrasonic power of 400 W for 24 h to obtain isopropanol (IPA)-MoS with a concentration of 171 mg / L. 2 Nanosheet dispersion;
[0071] S3: Place 0.055 g Fe 2 O 3 Add Fe-MOF powder to 6.55 ml IPA-MoS 2 The nanosheet dispersion was ultrasonically mixed for 30-90 minutes to obtain MoS 2 / Fe 2 O 3 @Fe-MOF composite material dispersion;
[0072] S4: MoS obtained from S3 2 / Fe 2 O 3 After the Fe-MOF composite material dispersion was ultrasonically mixed with 0.45 ml ethanol, 0.015 g carbon black and 50 μl perfluorosulfonic acid polymer Nafion D520 were added, and stirring was continued for 30-90 minutes. The mixed solution was coated on the surface of the carbon plate and dried at room temperature to obtain MoS 2 / Fe 2 O 3 @Fe-MOF modified carbon electrode, in which MoS 2 In MoS 2 / Fe 2 O 3 @The doping ratio of Fe-MOF composite material is 2%.
[0073] Comparative Example 1
[0074] A Fe 2 O3 The preparation method of @Fe-MOF modified carbon electrode comprises the following steps:
[0075] S1: 1.5 mol FeCl 3 6H 2 O was added to 20 ml of deionized water, stirred to dissolve, 20 ml of ethanol and 20 ml of N, N-dimethylformamide DMF were added and mixed, and then 1 mol of trimesic acid was added and stirred to dissolve, and 20 ml of polyvinyl pyrrolidone K30 was added. After stirring at room temperature for 60 min, the mixture was transferred to a reactor for hydrothermal reaction at 160 ° C for 3 h. After the reaction was completed, the mixture was naturally cooled to room temperature and centrifuged. The separated solid was washed and dried to obtain Fe 2 O 3 @Fe-MOF powder;
[0076] S2: 0.055 g Fe 2 O 3 Add 7 ml of ethanol to the Fe-MOF powder to fully disperse it, then add 0.015 g of carbon black and 50 μl of perfluorosulfonic acid polymer Nafion D520, continue stirring for 30-90 minutes, apply the mixed solution on the surface of the carbon plate, and dry it at room temperature to obtain Fe 2 O 3 @Fe-MOF modified carbon electrode.
[0077] Comparative Example 2
[0078] A method for preparing a MOF-modified carbon electrode comprises the following steps:
[0079] S1: 1.5 mol FeCl 3 6H 2 O was added into 20 ml of deionized water, stirred to dissolve, and then 1 mol H 3 BTC, stirred at room temperature for 60 min, transferred to a reactor for hydrothermal reaction at 160 °C for 12 h. After the reaction was completed, it was naturally cooled to room temperature and centrifuged. The separated solid was washed and dried to obtain Fe-MOF powder.
[0080] S2: Add 0.055 g Fe-MOF powder to 7 ml ethanol to fully disperse it, then add 0.015 g carbon black and 50 μl perfluorosulfonic acid polymer Nafion D520, continue stirring for 30-90 minutes, apply the mixed solution on the surface of the carbon plate, and dry it at room temperature to obtain a Fe-MOF modified carbon electrode.
[0081] Test Example 1
[0082] The Fe prepared in Example 1-4 2 O 3 @Fe-MOF was subjected to X-ray diffraction (XRD) crystal structure analysis. The specific test results are given by Figure 2 As shown. Figure 2 Display: Fe 2 O 3 The XRD pattern of the Fe-MOF sample is consistent with the diffraction peak position and peak shape of hematite and MOF corresponding to the standard chart, proving that Fe 2 O 3 @Fe-MOF was successfully prepared. In addition, according to Figure 2 The intensity of each diffraction peak shows that with the increase of hydrothermal reaction time, the peak intensity of hematite diffraction peak increases and the peak intensity of MOF diffraction peak decreases. Therefore, the hydrothermal time can be adjusted to control the Fe 2 O 3 / Fe-MOF composite material composition ratio to achieve controllable preparation of the composite material composition.
[0083] Test Example 2
[0084] The MoS prepared in Example 1 2 / Fe 2 O 3 @Fe-MOF was characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The specific test results are as follows Figure 3 , Figure 4 As shown. Figure 3 Display: Fe 2 O 3 @Fe-MOF presents smooth spheres of uniform size and good dispersion. Figure 4 It can be observed that MoS 2 In thin flake state and evenly distributed in Fe 2 O 3 @Fe-MOF ball surface, realizing the composite of materials.
[0085] Test Example 3
[0086] The MoS prepared in Example 1 2 / Fe 2 O 3 @Fe-MOF was subjected to X-ray diffraction (XRD) crystal structure analysis. The specific test results are as follows Figure 5 The XRD patterns of the samples are consistent with those of hematite, MOF, and MoS 2 The diffraction peak position and peak shape are consistent with those of MoS 2 Successfully compounded with Fe 2 O 3 @Fe-MOF on.
[0087] Test Example 4
[0088] The electrodes prepared in Examples 1-6 and Comparative Examples 1-2 were used as cathodes in a bio-electro-Fenton (BEF) system to measure the battery power density curve. The maximum power density of a battery can characterize the power generation performance of the battery, such as Figure 6 As shown, MoS 2 / Fe 2 O 3 The power density of the battery with the Fe-MOF electrode as the cathode (i.e., Examples 1 to 6) is higher than that of Comparative Example 1 (Fe 2 O 3 The maximum power density of the Fe-MOF electrode is 93.20 mW / m 2 ) and Comparative Example 2 (the maximum power density of the Fe-MOF electrode is 76.84 mW / m 2 ), and the hydrothermal reaction time, MoS in the composite electrode material 2 Doping ratio affects MoS 2 / Fe 2 O 3 @Fe-MOF modified electrode power density. 2 / Fe 2 O 3 @Fe-MOF modified carbon electrode (hydrothermal reaction time is 3h, MoS 2 The power density of the battery with a doping ratio of 1%) as the cathode is the highest (135.34 mW / m 2 ). This indicates that the derivatization of Fe-MOF into Fe 2 O 3 @Fe-MOF electrode material effectively improves the power generation performance of the battery. MoS is doped on its surface 2 It can further promote its electron transport ability.
[0089] The electrodes prepared in Example 1 and Comparative Examples 1-2 were subjected to cyclic voltammetry (CV) tests. Figure 7 As shown in the figure, the cyclic voltammetry (CV) test results can be used to analyze the MoS 2 / Fe 2 O 3 @Fe-MOF modified carbon electrode (MoS 2 In MoS 2 / Fe 2 O 3 @Fe-MOF composite material doping ratio is 1%) and comparative example 1 (Fe 2 O 3The peak area and redox peak current of the CV curve are important indicators of the electrochemical activity of electrode materials. A larger peak area and a higher redox peak current usually mean that the material can transfer electrons more efficiently in the electrochemical reaction and provide more reaction sites. 2 O 3 @Fe-MOF electrode Compared with Fe-MOF electrode, MoS 2 / Fe 2 O 3 @Fe-MOF modified carbon electrode showed a larger peak area and higher redox peak current, indicating that it has strong electrocatalytic performance.
[0090] The electrodes prepared in Example 1 and Comparative Examples 1-2 were subjected to electrochemical impedance spectroscopy (EIS) tests. Figure 8 As shown in the figure, the electrochemical characteristics of different electrode materials are analyzed by the semicircle diameter of the Nyquist curve. A smaller semicircle diameter indicates a lower charge transfer resistance, which means that the electron transfer in the electrochemical reaction process is smoother and the reaction rate is faster. 2 O 3 @Fe-MOF electrode) and Comparative Example 2 (Fe-MOF electrode), the MoS 2 / Fe 2 O 3 The semicircle diameter of the Nyquist curve of the @Fe-MOF modified carbon electrode is the smallest, indicating that its charge transfer resistance is lower and the electron transfer rate is faster.
[0091] Test Example 5
[0092] The modified carbon electrodes prepared in Examples 1, 5, and 6 and Comparative Examples 1-2 were placed in the constructed dual-chamber BEF system as cathodes, and degradation experiments were carried out on 10 mg / L tetracycline (TC) simulated wastewater in the cathode chamber. The test results are shown in Figure 2. Fig. 9 shown.
[0093] 1% MoS of Example 1 2 / Fe 2 O 3 @Fe-MOF electrode, 0.5% MoS in Example 5 2 / Fe 2 O 3 @Fe-MOF electrode, 2% MoS in Example 6 2 / Fe 2 O 3 @Fe-MOF electrode, Fe of Comparative Example 1 2 O 3The degradation rates of TC by the BEF system constructed by the Fe-MOF electrode of @Fe-MOF electrode and the Fe-MOF electrode of comparative example 2 were 99.47%, 91.26%, 94.56%, 88.96% and 74.46%, respectively. 2 / Fe 2 O 3 @Fe-MOF modified carbon electrode BEF system has a significantly higher degradation effect on pollutants than Fe 2 O 3 @Fe-MOF modified carbon electrode and Fe-MOF modified carbon electrode bio-electro-Fenton (BEF) system, demonstrating that MoS 2 / Fe 2 O 3 @Fe-MOF modified carbon electrode has high catalytic performance for the degradation of pollutants.
Claims
1. A method for preparing a MoS2 / Fe2O3@Fe-MOF modified carbon electrode, characterized in that: The steps include: S1: Add trivalent iron salt to deionized water, stir to dissolve, add ethanol and N, N-dimethylformamide DMF to mix, then add trimesic acid, stir to dissolve, add polyvinyl pyrrolidone K30, stir at room temperature for 60 min, transfer to a reactor for hydrothermal reaction, the reaction temperature is 160 ° C, the time is 3 h, after the reaction is completed, naturally cool to room temperature, centrifuge, separate the solid, wash and dry to obtain Fe2O3@Fe-MOF powder; wherein, the volume ratio of deionized water, ethanol, and N, N-dimethylformamide is 1:1:1, the concentration of polyvinyl pyrrolidone K30 in the solution is 20g / L, and the mass ratio of trivalent iron salt to trimesic acid is 1.5-2:1; S2: After natural molybdenite is ball-milled and sieved into powder, it is added into isopropyl alcohol IPA and subjected to ultrasonic exfoliation to obtain an isopropyl alcohol IPA-MoS2 nanosheet dispersion; wherein the particle size of the natural molybdenite powder is ≤20µm, and the concentration of the isopropyl alcohol IPA-MoS2 nanosheet dispersion is 171mg / L; S3: adding the Fe2O3@Fe-MOF powder obtained in S1 to the isopropyl alcohol IPA-MoS2 nanosheet dispersion obtained in S2, and ultrasonically mixing for 30-90 minutes to obtain a MoS2 / Fe2O3@Fe-MOF composite material dispersion, wherein the doping ratio of MoS2 in the MoS2 / Fe2O3@Fe-MOF composite material is 0.5-2%; S4: After ultrasonically mixing the MoS2 / Fe2O3@Fe-MOF composite material dispersion obtained in S3 with ethanol, add carbon black and perfluorosulfonic acid polymer Nafion D520, stir for 30-90 min, coat the surface of the carbon electrode, and dry at room temperature to obtain a MoS2 / Fe2O3@Fe-MOF modified carbon electrode.
2. The method for preparing the MoS2 / Fe2O3@Fe-MOF modified carbon electrode according to claim 1, characterized in that: In the S1, the trivalent iron salt is FeCl3·6H2O or Fe(NO)3·9H2O.
3. The method for preparing the MoS2 / Fe2O3@Fe-MOF modified carbon electrode according to claim 1, characterized in that: In the S1, the concentration of the deionized water solution of the ferric salt is 75-100 mol / L.
4. The method for preparing the MoS2 / Fe2O3@Fe-MOF modified carbon electrode according to claim 1, characterized in that: In S2, the solid-liquid ratio of natural molybdenum ore powder and isopropyl alcohol IPA is 1:
200.
5. The method for preparing the MoS2 / Fe2O3@Fe-MOF modified carbon electrode according to claim 1, characterized in that: In S2, the power of ultrasonic peeling is 350 W and the time is 24 h.
6. The method for preparing the MoS2 / Fe2O3@Fe-MOF modified carbon electrode according to claim 1, characterized in that: In the S4, the volume ratio of the MoS2 / Fe2O3@Fe-MOF composite material dispersion to ethanol is 1:0.07-3.5; the mass ratio of carbon black to the MoS2 / Fe2O3@Fe-MOF composite material is 0.25-0.3:1; the mass ratio of the perfluorosulfonic acid polymer Nafion D520 to the MoS2 / Fe2O3@Fe-MOF composite material is 1-1.3:
1.
7. The method for preparing the MoS2 / Fe2O3@Fe-MOF modified carbon electrode according to claim 1, characterized in that: In S4, the carbon electrode is a carbon plate, carbon felt or carbon cloth.
8. An application of a MoS2 / Fe2O3@Fe-MOF modified carbon electrode prepared by the method for preparing a MoS2 / Fe2O3@Fe-MOF modified carbon electrode according to any one of claims 1 to 7, characterized in that: The MoS2 / Fe2O3@Fe-MOF modified carbon electrode is used as the cathode of the bioelectric Fenton system to degrade antibiotics in sewage.
Citation Information
Patent Citations
Molybdenum sulfide / ferric oxide composite material and preparation method and application thereof
CN106783201A
Fe-pCOFs-MWCNTs / MoS2 nano composite material as well as preparation method and application thereof
CN116814039A
Metal-organic framework electrodes for sodium ion batteries
US20180053968A1